GP198 omething wicked this way comes. The first paediatric cases of enterovirus D68-associated acute flaccid myelitis in Ireland. (June 2019) - Kennedy, Elaine; deGascun, Cillian; Waters, Allison; Drew, Richard; Butler, Karina; Gavin, Patrick
Abstract : Introduction: Enterovirus (EV) D68 is a non-polio enterovirus closely related to rhinovirus. In contrast to the majority of EV, EV D68 is primarily a respiratory virus. However, like polio and EV D71, EV D68 displays neurotropism and the ability to cause acute flaccid myelitis. Acute flaccid myelitis (AFM) refers to acute flaccid limb weakness with predominantly gray matter spinal cord lesions on imaging or evidence of anterior horn cell damage on electrodiagnostic studies. In 2014, in the midst of a large outbreak of EV D68-associated respiratory disease in the United States, clusters of AFM were noted in children. Enhanced nationwide surveillance ultimately identified 120 cases of AFM. Enterovirus D68 was the most common virus detected in these patients. Full recovery was rare (5%). More recently, a 2019 report describes 29-cases of EV D68-associated AFM diagnosed in 12 European countries in 2016. We present the first cases of EV D68-associated AFM in Ireland to date. Clinical cases: In June 2016, a previously well 2-year 9 month old girl presented with a one-week history of cough, fever and vomiting. Thirty-six hours later, respiratory status worsened and she developed AFM and bulbar palsy necessitating intubation and ventilation. CSF analysis demonstrated a lymphocytic pleocytosis. In October 2018, a 4-year old boy, with a background of acute lymphoblastic leukaemia diagnosed 17-months previously, presented with fever, worsening cough and pancytopenia. Three-days later, he required intubation and ventilation after a respiratory arrest. On weaning sedation, eight-days later, he displayed clinical signs of AFM. Both children had nasopharyngeal aspirates (NPA) PCR positive for rhinovirus/enterovirus, and stool/rectal swabs PCR positive for EV. CSF was PCR negative for EV, HPE, HSV, HHV-6, VZV and adenovirus. MRI showed extensive abnormal signal predominantly of white matter in the cervico-thoracic cord. Electromyography was indicative of anterior horn cell involvement. Both children required prolonged ICU and hospital stays, have severe residual neurologic deficits with flaccid quadriparesis, tracheostomy and require ongoing ventilatory support. Results: Subsequent subtyping of EV isolates from both children was positive for EV D68. Additional testing of 800 rhinovirus/enterovirus-positive NPA specimens submitted to the National Virus Reference Laboratory (NVRL) from August to October 2018 detected 30 (3.75%) EV D68-positives. Conclusion: This report of two-children with rapidly progressive AFM following prodromal febrile respiratory or gastrointestinal illness in association with EV D68 infection and recent results of enhanced European and local surveillance suggests that EV D68 AFM has arrived in Ireland.